Real-time DNA detection using Pt nanoparticle-decorated reduced graphene oxide field-effect transistors - Yin, Zongyou (2013)
A large-area, continuous, few-layer reduced graphene oxide (rGO) thin film has been fabricated on a Si/SiO2 wafer using the Langmuir–Blodgett (LB) method followed by thermal reduction. After photochemical reduction of Pt nanoparticles (PtNPs) on rGO, the obtained PtNPs/rGO composite is employed as the conductive channel in a solution-gated field effect transistor (FET), which is then used for real-time detection of hybridization of single-stranded DNA (ssDNA) with high sensitivity (2.4 nM). Such a simple, but effective method for fabrication of rGO-based transistors shows great potential for mass-production of graphene-based electronic biosensors.